Strategie budowania intymności – pierwsze listy Felicjana Medarda Faleńskiego i Marii Trębickiej - Agnieszka Bąbel (Napis, 2022)
This editorial article is a study on the letters numbered as the first and fourth from the collection of engagement correspondence between poet and translator, Felicjan Faleński, and writer, publicist and translator, Maria Trębicka, from 1854–1860, kept in the Jagiellonian Library in Kraków, volume 5780. The set of letters in Polish is composed of 626 pages in 4º format. It comprises 81 letters from Felicjan Medard Faleński (1825–1910) to Maria Trębicka (1821–1896), his wife from 1859, as well as 151 letters from Maria Trębicka to Felicjan Faleński in chronological order (though not free from errors). The article depicts the strategies used by Faleński and Trębicka to establish a bond and build a space of intimacy between the participants of the correspondence in the context of communication and psychological theories. The poet achieves this purpose not only by enchanting the addressee with his erudition and originality (assuming the mask of an eccentric, or Don Quixote) and making references to literary knowledge and outlooks they shared, but also by taking more sophisticated steps. These include the highlighting of a meta-literary character of a letter, or an invitation to transgressing linguistic and social norms (e.g. revealing details of private life, introspecting on his own character, or encouraging to break the world’s conventions together). Trębicka’s letter creates an image of her as an excellent listener, emphatic and well-read, who will allow the interlocutor to show his best side. For both of them, the correspondence space of intimacy builds a ‘second reality’, allowing for a sincere expression of emotions, hopes and fears. Their letters are similar to intimate diaries, in which the necessary contact with the recipient enables both self-knowledge and self-creation.